Model Manajemen Pemasaran Buah Jeruk Di Kecamatan Besitang Kabupaten Langkat - Wahyu Ziaulhaq (Formosa Journal of Science and Technology, 2022)
This study aims to describe the marketing management model of citrus fruits in Besitang sub-district, Langkat district. The purpose of this research is to educate readers that marketing is the most important thing so that the distribution of citrus fruits can be spread throughout Langkat Regency so that citrus fruits can be obtained by the community in the market and farmers get profit from the marketing results. The research method used is qualitative. The approach used is an anthropological and sociological approach. Data collection techniques are through observation and unstructured interviews, after the data is obtained, the data is analyzed scientifically. The results of the research that have been found indicate that first, oranges have economic value so that marketing management is the most important thing. Second, citrus fruits are not able to last long, only for a few weeks, so the marketing must really be accommodated, third. Citrus fruit marketing is distributed to traditional markets and supermarkets.